Evaluation by Computer Simulation of the Operation of a Fleet of Drones for Transporting Materials in a Manufacturing Plant of Plastic Products - Cordova-Gonzalez, F; Olivares-Chiappa, V (Institute of Electrical and Electronics Engineers Inc., 2016)
In many manufacturing plants, there is a major problem in the internal logistics due to the high number of products, machines, and routes, especially in those manufacturing plants that produce low weight products. For example, a manufacturer of plastic is used as a reference model. In this situation, the final product, storage boxes for home of various sizes, are assembled by performing «pickup» of parts in warehouses and performing «delivered» to the assembly lines at the plant. This work is aimed to simulate and evaluate a model which represents the operation of a fleet of drones in the process of transporting materials. The model also includes the manufacture of semi-finished materials and parts in their respective workstations and final assembly of the products in their respective lines. This model allows evaluating the impact on production due to inventory reduction of materials in process, changes in the capacity of productive resources, especially the drones used for transport. © 2015 IEEE.